Perkiraan sedimentasi Pada Tahun 2018 di Waduk Jatiluhur, Kabupaten Purwakarta: Sedimentation Prediction in Jatiluhur DAM, Purwakarta District - Ulfah Sarach Sheftiana; M Yanuar Jarwadi Purwanto; Suria Darma Tarigan (Jurnal Ilmu Tanah dan Lingkungan, 2021)
Jatiluhur DAM is one of the multipurpose DAMs in West Java with the design of hydroelectric power plants, water supply in industry, irrigation, fisheries, tourism and flood control. Based on the final report of Juanda Public Corporation in 2000 that the DAM volume in 1964 was 2,970 million m³, in 1987 it was 2,556 million m³, 1995 was 2,456 million m³ and in 2000 was 2,448 million m³. This shows that the DAM volume has decreased by 522 million m³ over a period of 36 years at an altitude of ± 107 masl. The purpose of this study are to calculate sedimentation in the Jatiluhur DAM in 2018. TSS measurements using SNI 06-6989.3-2004 and calculation of sedimentation using direct measurement methods. The results showed that the total sediment in DAM inlet is 859,368.40 tons year-1 and the reservoir outlet is 92,553.33 tons year-1. Based on this data, the total sediment deposited in the Jatiluhur Reservoir in 2018 was 766,815.07 tonnes. So it needs handling in reducing sediment so that the reservoir does not experience silting.